2018
DOI: 10.4236/oalib.1104881
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Entrepreneurial Intention within University Students in Egypt

Abstract: The current research aims to propose a framework of the effects of behavioral factors of theory of planned behavior and psychological traits factors on students' entrepreneurial intention, measuring the size of effect, the circumstances under which the effect is clearly observed and studying the weighted effect of each of the behavior and traits elements. A questionnaire was adopted from previous studies and directed to students in the Egyptian universities. A total number of 430 respondents were considered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
3
17
1
1
Order By: Relevance
“…Some prior research shows a positive relation between need for achievement and entrepreneurial intention (Gürol and Atsan, 2006;Çolakoğlu and G zükara, 2016). However, this is in contrast with the findings of a recent study carried out by Sharaf et al (2018) who reported that the need for achievement has no significant impact on entrepreneurial intention.…”
Section: Need For Achievementcontrasting
confidence: 99%
“…Some prior research shows a positive relation between need for achievement and entrepreneurial intention (Gürol and Atsan, 2006;Çolakoğlu and G zükara, 2016). However, this is in contrast with the findings of a recent study carried out by Sharaf et al (2018) who reported that the need for achievement has no significant impact on entrepreneurial intention.…”
Section: Need For Achievementcontrasting
confidence: 99%
“…Fig 1 is the base model according to Ajzen’s (TPB) [ 15 ], while Fig 2 is based on Lüthje & Franke’s Model (LFM) [ 17 ]. Previous studies were used as guides for distinguishing these models [ 21 , 65 ]. The base model predicts that attitudes concerning entrepreneurship, social norms and perceived behavioural control are positively associated with students’ self-employment intention.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Someprior research shows a positive relation between need for achievement and entrepreneurial intention (Çolakoğlu & Gözükara, 2016;Gürol & Atsan, 2006). However, Sharaf et al (2018) and Sesen (2013) found different results in studies on university students in Egypt and Turkey; they came to the conclusion that the need for achievement has no significant effect on entrepreneurial intention.…”
Section: Personality Traitsmentioning
confidence: 96%